Development of Islamic Character of Pulo People Through Folklore as Local Wisdom of the Tidung Island Community - Siti Gomo Attas; Gres Grasia Azmin; Marwiah Marwiah (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2022)
The development of the Islamic character of the Pulo people through the folklore of Panglima Hitam and Raja Tidung as local wisdom of the people of Tidung Island. Tidung Island, which is now a tourist destination, is slowly undergoing changes in the lives of the island's people who were originally a fishing community, now turned into a tourist destination. The shift in function which originally had a fishing tradition turned into a tourist resort that is ready to accommodate the coffers of tourists who come and go to Tidung Island. The existence of Tidung Island is recorded in an oral tradition of folklore that is still known by the people, namely the Panglima Hitam folklore and the story of Raja Tidung. The value of Islamic character as local wisdom is used to read the two folk tales, especially the character development of the younger generation on Tidung Island. The Islamic character of the island community that must be developed includes: (1) moral values ​​to God, (2) moral values ​​to others, and (3) moral values ​​to oneself. These three Islamic characters serve as character models used by the community to develop the potential of the Tidung Island community.